Passage Territories: Reframing Living Spaces in Contested Contexts - Paramita, Kristanti Dewi; Schneider, Tatjana (UI Scholars Hub, 2018)
This paper investigates the concept of ‘passage territories’ (Sennett, 2006), as living spaces constructed from one’s passage of movement from one separate space to another, and how it extends the discussion of interiority in contested contexts. Through observations of living spaces and the narrative accounts of dwellers’ in Kampung Pulo and Manggarai neighbourhoods of Jakarta, this study draws attention to the interiority of dispersed and layered spaces occupied by the kampungs’ dwellers. In this context, passage territories are driven by a) a limitation of space that, in turn, triggers the need to acquire more space; b) the occupation of a dweller that necessitates different types of space; and c) the limited access to infrastructural resources that influence the extent of a living space’s dispersal. Through the use of drawings, this study reveals the complete interiority of living spaces consisting of spaces with diverse spatial ownerships and scales. The boundaries of passage territories tend to be defned by the frequency and length of time needed for an activity instead of the relative proximity between certain spaces. Furthermore, the way objects are placed also shapes the boundaries of passage territories, both for permanent and temporary use of space. This paper then discusses the impact of this knowledge on the interiority of passage territories, proposing to use mechanisms of ‘patches’ and ‘corridors’ to shape the interior of territory that cross, share, and change into one another.